Direct visualization of critical hydrogen atoms in a pyridoxal 5′-phosphate enzyme. Issue 1 (December 2017) - Dajnowicz, Steven; Johnston, Ryne; Parks, Jerry; Blakeley, Matthew; Keen, David; Weiss, Kevin; Gerlits, Oksana; Kovalevsky, Andrey; Mueser, Timothy
Abstract Enzymes dependent on pyridoxal 5′-phosphate (PLP, the active form of vitamin B6 ) perform a myriad of diverse chemical transformations. They promote various reactions by modulating the electronic states of PLP through weak interactions in the active site. Neutron crystallography has the unique ability of visualizing the nuclear positions of hydrogen atoms in macromolecules. Here we present a room-temperature neutron structure of a homodimeric PLP-dependent enzyme, aspartate aminotransferase, which was reacted in situ with α-methylaspartate. In one monomer, the PLP remained as an internal aldimine with a deprotonated Schiff base. In the second monomer, the external aldimine formed with the substrate analog. We observe a deuterium equidistant between the Schiff base and the C-terminal carboxylate of the substrate, a position indicative of a low-barrier hydrogen bond. Quantum chemical calculations and a low-pH room-temperature X-ray structure provide insight into the physical phenomena that control the electronic modulation in aspartate aminotransferase. Pyridoxal 5'-phosphate (PLP) is a ubiquitous co factor for diverse enzymes, among them aspartate aminotransferase. Here the authors use neutron crystallography, which allows the visualization of the positions of hydrogen atoms, and computation to characterize the catalytic mechanism of the enzyme.